Transaksi Jual Beli Chip Game Online Higgs Domino - Masjulita Ritonga; Nurhotia Harahap (Jurnal El-Thawalib, 2022)
Higgs domino online game chip buying and selling transactions are transactions that are mostly carried out by higgs domino online game players, these chip buying and selling transactions are the same as buying and selling transactions in general. And the purchase of the higgs domino online game chip is done through social media or directly to the seller of the higgs domino online game chip, and regarding the price of the higgs domino online game chip which is traded based on an agreement between the seller and the buyer. The formulation of the research problem is how to practice buying and selling online high-domino game chips? And what about the perspective of fiqh, muamalah, buying and selling online game chips, higgs domino?. The purpose of this study is to obtain answers about how the practice of buying and selling online game chips higgs dominoes and knowing how the fiqh muamalah perspective on buying and selling online game chips higgs dominoes. This research is a field research that uses a descriptive qualitative approach in data collection. The data collection used in this research is the method of interview, observation, and documentation. The time in this study was about 3 months and the location of this research was in the village of Wek II Silayang Laying, North Padangsidimpuan District. This chip sale and purchase transaction has clear consent and qabul between the seller and the buyer, but the object being traded does not meet the pillars of buying and selling because the object being traded contains elements of maysir.